Exposure of students (pupils) and employees of educational institutions in the Leningrad region to natural sources of radiation Part 2: Hygienic assessment of doses and health risks depending on methods and approaches to measuring indoor radon concentration - A. S. Vasilyev (Радиационная гигиена)
For many years internal exposure to radon has been the main contributor to the annual dose to the population. The paper presents results of a hygienic assessment of doses and health risks for students (pupils) and employees of several educational institutions of the Leningrad region due to exposure to radon and its progeny, and also suggests the protocol for conducting measurements of indoor radon concentration in existing operated public buildings. Individual annual effective doses to students (pupils) and employees due to exposure to radon while in the building of an educational institution calculated on the basis of the results of instant measurements of radon EEC obtained in the normal operation mode of buildings ranged from 0.1 to 3.7 mSv/year for different institutions. However, calculation on the basis of the results of long-term measurements of radon concentration resulted in the dose values up to 10 times higher (from 0.2 to 22.9 mSv/year). Moreover, calculation on the basis of the results of instant measurements of radon EEC after leaving the premises for 12 hours with closed windows and doors according to the requirements of paragraph 6.5 of MU 2.6.1.2838-11 resulted in the dose values up to 7 times higher (from 0.1 to 13.5 mSv/year). Nevertheless, these high dose values do not reflect the real exposure scenario. According to the classification established in sanitary rules and norms OSPORB 99/2010, the exposure of students (pupils) and employees of several educational institutions can be classified as “increased” (from 5 to 10 mSv/year) or as “high” (more than 10 mSv/year) depending on methods and approaches to measuring indoor radon concentration. The average individual lifetime risk of radoninduced lung cancer death (based on the results of instant measurements of radon EEC obtained in the normal operation mode of buildings) for students (pupils) and employees of surveyed educational institutions ranged from 1.6∙10–4 to 1.4∙10–3. However, the usage of the results obtained with other methods and approaches to measuring indoor radon concentration, as a rule, did not lead to a significant increase in risk value, but in some cases it led to a change in the risk level category. The results of the assessment can be used to improve the method for indoor radon concentration monitoring in existing operated public buildings in the Russian Federation, which in turn will make it possible to obtain correct values of public doses and health risks.